Evaluation of a workplace health and wellbeing training course delivered online and face-to-face - Talati, Zenobia; Davey, E.; Grapes, C.; Shilton, Trevor; Pettigrew, Simone (Molecular Diversity Preservation International (MDPI), 2018)
Organisations may benefit from training champions to promote healthy workplace environments and initiatives. This study compared the perceived usefulness and relative effectiveness of an employee training course offered via online and face-to-face formats. Individuals who took part in the training course were assessed on their perceived competence and confidence to implement changes pre-and post-training. Repeated measures Analysis of Variance (ANOVA) and a t-test were conducted to test for significant differences between pre-and post-training scores and/or mode of training, respectively. Although the face-to-face training course was rated as slightly more useful, there were no significant differences between the two modes of training for the other dependent variables, and both modes led to significantly greater perceived competence and confidence post-training. These findings demonstrate the potential benefits of training employees to implement changes in their workplaces.